DESCRIPTION OF FALL RISK FACTORS ON FALLING INCIDENTS AMONG THE ELDERLY IN THE WORKING AREA OF KRUENG BARONA JAYA HEALTH CENTER - Syukriadi; Putra, Yadi; Fauziah; Akbar, Sulistia (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2022)
Immobility in the elderly can cause muscle stiffness, pain, and impaired movement, highlighting the need for families to understand the potential effects of immobilization beyond just taking special care of their elderly members. This study aims to describe the risk factors for falls among the elderly in the working area of Krueng Barona Jaya Health Center. A descriptive design using a cross-sectional approach was employed, with a sample of 65 respondents. The instrument used in this study was a questionnaire sheet. The findings revealed that the highest distribution of fall risk was in the high category, with 33 respondents (50.8%) at risk of falling. The study's outcomes can serve as a guide for healthcare professionals in providing appropriate services to elderly patients, particularly those at risk of falls.